Unraveling Large and Polyploidy Genome of the Crucifer Orychophragmus violaceus in China, a Potential Oil Crop - Qi Pan; Pan Zeng; Zaiyun Li (Plants, 2023)
The genus Orychophragmus in the Brassicaceae family includes the types with 2n = 20, 22, 24, and 48. The species O. violaceus (L.) O. E. Schulz has 2n = 24 and is widely cultivated as an ornamental plant in China. This review summarizes the research progress of its genome structure and evolution in the context of cytogenetics and genome sequencing. This species has a large genome size of ~1 Gb and longer chromosomes than those of Brassica species, which is attributable to the burst of TE insertions. Even more, one tetraploidization event from about 600–800 million years ago is elucidated to occur during its genome evolution, which is consistent with the polyploidy nature of its genome revealed by the meiotic pairing patterns. Its chromosomes are still characterized by a larger size and deeper staining than those from Brassica species in their intergeneric hybrids, which is likely related to their inherent differences between genome structures and cytology. Its genome is dissected by the development of additional alien lines, and some traits are located on individual chromosomes. Due to the abundant dihydroxy fatty acids in its seed oil with superior lubricant properties and wide environmental adaptations, this plant promises to be utilized as one new oil crop in the future.